(untitled) (Praxis Educativa, 2026)
What museums do we have and what museums do we want? Which approaches in art teacher education are urgent for revising certain museological projects? These are the questions that inspire the set of reflections presented here. The article starts from a historical perspective to contextualize museological projects and the importance and urgency, within the scope of art teacher education, of revising these ideas. In the final part, training experiences in the arts are presented as a way of creating territories of meaning for shared practices.